2011
DOI: 10.1007/s12010-011-9313-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteins of the Optic Ganglion in Octopus vulgaris Under Methanol Stress Revealed Using Proteomics

Abstract: An analytical approach using the two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) technique separated the proteome from the optic ganglia of Octopus vulgaris (OVOG). Approximately 600 protein spots were detected from the extraction when applying 150 μg protein to a 2D-PAGE gel in the pH range 5.0-8.0. Compared to the control, significant changes of 18 protein spots were observed in OVOG under the stress of native seawater containing 2% methanol for 72 h. Among these spots, we found that eight were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…7 and 8). Based on our knowledge and experience in proteomics, the biomarkers for monitoring should be considered as a group of differential proteins consisting of high frequency and individual proteins rather than single proteins [45,46]. Here, we indicated that the major apoptosis pathway of various cancer cells (including tumors) induced in vivo with CDDP were closely connected with the differential proteins shown in both Figs.…”
Section: Discussionmentioning
confidence: 66%
“…7 and 8). Based on our knowledge and experience in proteomics, the biomarkers for monitoring should be considered as a group of differential proteins consisting of high frequency and individual proteins rather than single proteins [45,46]. Here, we indicated that the major apoptosis pathway of various cancer cells (including tumors) induced in vivo with CDDP were closely connected with the differential proteins shown in both Figs.…”
Section: Discussionmentioning
confidence: 66%
“…The common octopus is a species with great food importance, since it is a complete food with great nutritional value and it is highly appreciated. Due to the high scientific interest and high commercial value of the common octopus, several transcriptomic and proteomic studies have been published, including adult specific organs [ 21 , 22 , 23 ] and paralarvae under different growth conditions [ 24 , 25 , 26 ]. However, the biological processes of this species are still not well understood due in part to this lack of genome sequencing and accurate annotation.…”
Section: Discussionmentioning
confidence: 99%
“…The toxic effect of methanol on the optic nerve and the retina may occur through the influence on the expression of key cytoskeleton proteins—actins and tubulins (beta-actin, beta-tubulin) conditioning the maintenance of the proper structure of cells, as well as cell signaling and regulating the process of apoptosis. In addition, changes in the expression of enzymes from the group of alcohol dehydrogenases: alcohol dehydrogenase (ADH), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), long-chain acetyl-CoA dehydrogenase (VLCAD), family 5 member aldehyde dehydrogenase A1 (ALDH5A1), dehydrogenase 2 monophosphate-5' (IMPDH2), as well as proteins from the crystallin group and heat shock proteins (HSP) were also observed (Chen et al 2012 ; Huang et al 2011 ).…”
Section: Methanol-induced Optic Neuropathy (Me-ion)mentioning
confidence: 99%